Performance of 40Gb/s modulation formats over non-zero dispersion shifted fiber (NZDSF) [electronic resource] - Dito Aldillah Haritsah, 1988- (2010)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2010